DAMAI DI HATI, DAMAI DI BUMI -Narasi Damai dari Pinggiran Pondok Pesantren Anwarul Huda - Yosafat Roni Sentosa (Litbang STFT Widya Sasana Malang, 2015)
Our daily life is full of news connected with terrorism in the name of religion. This is not only a disturbing thing but also put our peaceful living together on the brink. Being struck by the fact that ordinary people live peacefully in perifery of Malang, I would propose a research on how they conceive peace in lived experience. So, I go to “Pondok Pesantren of Anwarul Huda” to listen to their concerns as well as opinions and hopes on living peacefully with other people. From my perspective their ideas are indeed beautiful lesson not just narrated but also to be explored. Keywords: Damai di hati, fundamentalisme, silaturahmi, narasi, persahabatan.